Morphological and protein analyses of adult female salivary glands of Anopheles barbirostris species A1 (Diptera: Culicidae) - B. Phattanawiboon (2018)
Morphology and protein profiles of female salivary glands of Anopheles barbirostris species A1 were analyzed. Female glands consisted of a distinctive tri-lobed structure connected to a main salivary canal, a single medial and two lateral lobes with proximal and distal portions. Cellular architecture was similar among the lobes, with secretory material appearing as large masses. Cells of the proximal-lateral lobes contained secretory masses with a finely filamentous aspect. In the distal-lateral lobes, cells had a dense secretory product with mottled pattern. Cells of the medial lobe had secretory masses which were uniformly stained and highly electron dense. Following emergence, the glands accumulated secretory material rapidly and developed completely within three days. Degenerative changes including loss of stored secretion and increase of cytoplasmic vacuolation and concentric lamellar structures were observed from day 16 post emergence that correlated with total amount of the salivary gland proteins determined during development. SDS-PAGE, nanoLC-MS, and glycoprotein analysis revealed at least eleven major protein bands, of which each morphological region contained different major proteins. Two glycoproteins, apyrase/5'-nucleotidase and D7, were identified. These results form a basis for further studies on details of cytopathological changes of malarial infected glands and roles of the proteins in disease transmission.